Comparison of perioperative analgesia between posterior stabilized and posterior cruciate retaining prostheses following total knee arthroplasty - Xing Jin; Jingjing Liu; Qiang Yang; Chengxin Ji; Shanshan Song; Dan Zhao; Xiaodong Pei; Lei Sun (Scientific Reports)
Abstract Background Posterior-stabilized (PS) and posterior cruciate retaining (CR) prostheses constitute the most widely used knee prostheses. This study aimed to determine the effects of PS and CR prostheses on postoperative analgesia following total knee arthroplasty (TKA) and provide a reliable clinical basis for optimizing postoperative analgesic effects. Methods Overall, 120 consecutive patients were enrolled in this study and classified into PS (n = 60) and CR (n = 60) groups according to the type of prosthesis used. All patients underwent TKA along with spinal anesthesia. All patients received adductor canal block (ACB) and periarticular infiltration (PAI) for postoperative analgesia. The primary outcomes comprised visual analog scale (VAS) scores at rest and during movement (extension and flexion exercises) measured till 72 h postoperatively. Secondary outcomes were as follows: preoperative VAS scores, preoperative hospital for special surgery knee scores, tourniquet duration, and femur and tibia osteotomies. Results The 12-h postoperative VAS scores at rest and during movement were significantly lower in the CR group than in the PS group (0.71 ± 1.36 vs. 1.36 ± 0.95 and 2.02 ± 1.85 vs. 2.81 ± 1.25, P < 0.05). The 24-h postoperative VAS scores at rest were significantly lower in the CR group than in the PS group (1.85 ± 1.40 vs. 2.47 ± 0.97, P < 0.05). There were no significant differences in the VAS scores between the groups at other timepoints at rest and during movement. Tourniquet duration was significantly shorter in the CR group than in the PS group (82.57 ± 11.12 min vs. 73.10 ± 10.74 min, P < 0.05). There were no significant differences in the extent of osteotomies on the medial and lateral sides of the femur and tibia between the groups. Conclusion At 24 h after surgery, multimodal analgesia with ACB and PAI provides better analgesic effects in patients who undergo CR prosthesis replacement compared with those who undergo PS prosthesis replacement.